Interview with Max Presneill, LA-based artist and curator, Brisbane, Australia, 12 May 2017 - Messham-Muir, Kit (2017)
Five years ago, Max Presneill was one of the very first artists I interviewed for the StudioCrasher project. I caught up with Max again while he was in Brisbane, Australia, for the opening of his solo exhibition at TW Fine Art. In this interview, I Max talks about how his studio practice has evolved since our first interview, moving from figuration to abstraction.